Morphine Versus Methadone Treatment for Neonatal Withdrawal and Impact on Early Infant Development - Sharon Burke MD; Anna Malia Beckwith MD (SAGE Publishing, 2017)
Objective . Compare developmental outcomes in infants treated with morphine versus methadone. Method . Retrospective chart review of newborns identified through use of ICD-9 code for neonatal abstinence syndrome (NAS). Thirty-six infants were evaluated-17 treated with methadone and 19 treated with morphine. Assessment was completed following treatment using the Bayley Scales of Infant and Toddler Development-Third Edition (Bayley-III). Scores in Cognitive, Language, and Motor domains were compared. Results . Comparison of scores between morphine- and methadone-treated groups revealed differences in mean Cognitive Composite (91.3 vs 83.0; P = .03410) and mean Total Motor Composite Scores (96.3 vs 89.6; P = .0149). Conclusion . Newborns with NAS treated with morphine had significantly higher scores in Cognitive and Gross Motor domains compared to infants treated with methadone. Development screening should be pursued to determine if this difference persists throughout early childhood. Results may influence accepted treatment protocols for NAS.